Labour Supply and Childcare: Allowing Both Parents to Choose - Karen A. Mumford; Antonia Parera-Nicolau; Yolanda Pena-Boquete (Institute of Labor Economics (IZA), 2019)
We develop and estimate a structural model of labour supply for two parent families in Australia, taking explicit account of the importance of childcare related variables. Our main contribution is to consider the labour supply decisions of both parents and their choice of childcare simultaneously. Labour supply decisions of mothers are found to be substantially more responsive to changes in their own wage (at intensive and extensive margins) than is the case for fathers, with minimal cross-wage labour supply responses from fathers. Our results imply that policies increasing the wage of mothers will be associated with marked increases in labour market participation and in the working hours of mothers in the Australian labour market, with little offsetting decline in the labour supply of fathers.
Keywords: J00; J13; J22; 330; childcare; parental labour supply; discrete; unitary